MICRONUTRIENTS (Fe, Cu, Zn) IN CACAO BEANS FROM COASTAL AREA OF EAST LUWU REGENCY - Yunita Pare Rombe; Alfian Noor; Nursiah La Nafie; Asma Assa (Marina Chimica Acta, 2019)
Cacao is an excellent essential minerals source. Cacao is a raw material for various products with rich mineral content to fulfill the nutritional requirements of human body, both for children and adults. Micronutrients of sufficient quantities greatly determines the nutritional quality of the food. Micronutrients content that in the body functions as a cofactor for certain enzymes involved in metabolism . This study aims to find out the micronutrients content in cacao beans from 5 location points and its potential to be utilized as food products raw material which meet the body nutritional requirement. This study  will be conducted at 5 locations point. Methods of analysis  used digestion and Inductively Coupled Plasma. Study findings that micronutrients content in cacao beans from 5 location points  were: copper (Cu), iron (Fe), and zinc (Zn) at average 2.316 mg/100g, 3.99 mg/100g, and  5.917 mg/100g, respectively.